The modern construction of myth - Von Hendy, Andrew, 1932- (Indiana University Press, 2001)
Andrew Von Hendy offers an integrated critical account of the career of myth in modernity. He takes as its starting point some crucial moments in the 18th-century reinvention of the concept and then follows the major branches of theorizing as they appear in the work of theologians, philosophers, literary artists, political thinkers, folklorists, anthropologists, psychologists, and others.